ANALISIS FAKTOR-FAKTOR KEUANGAN TERHADAP RETURN SAHAM (Studi Empiris Perusahaan Terideks LQ45 Periode 2015-2019) - Safitri, Dewi Nur; Kusumawati, Eny (Prosiding University Research Colloquium, 2021)
This study aims to determine the effect of liquidity, profitability, cash flow, solvency, and market ratios on stock returns. In this study, liquidity is proxied by the current ratio, profitability is proxied by the net profit margin, solvency is proxied by the debt to equity ratio, and the market ratio is proxied by earnings per share. This research was conducted on companies listed on the LQ45 index of the Indonesia Stock Exchange (IDX) for the period 2015-2019. The sampling technique used in this study was purposive sampling technique. The sample used in this study were 25 companies and conducted for 5 years to produce 125 data. The data analysis technique used is multiple linear regression analysis. The results showed that the variables of liquidity and profitability had an effect on stock returns, while the variables of cash flow, solvency, and market ratios had no effect on stock returns.